ENT secrets - Scholes, Melissa A.; Ramakrishnan, Vijay R. (Philadelphia, PA : Elsevier Inc., 2023)
For more than 30 years, the highly regarded Secrets Series® has provided students and practitioners in all areas of health care with concise, focused, and engaging resources for quick reference and exam review. ENT Secrets, 5th Edition, offers practical, up-to-date coverage of the full range of essential topics in this dynamic field. This highly regarded resource features the Secrets' popular question-and-answer format that also includes lists, tables, pearls, memory aids, and an easy-to-read style - making inquiry, reference, and review quick, easy, and enjoyable." --
1 General. -- 2 Head and neck. -- 3 Allergy and rhinology. -- 4 Otology and audiology. -- 5 Pediatric otolaryngology. -- 6 Facial plastic surgery, reconstruction, and trauma. -- 7 Laryngology and swallowing disorders. -- Index
Keywords: Otolaryngology; Otolaryngology ; Examinations, questions, etc. -- Examinations, -- questions, etc